Media Manipulation to Enhance In Vitro Pitcher Formation in Nepenthes mirabilis (Lour.) Druce for Microfloriculture Development - Sugiyono Sugiyono; Anindya Puspaning Tyas; Dea Yuniar Indikasuri; Sri Lestari; Paul A Davison; Rendie Prasetyo (Universitas Sebelas Maret, 2025)
Microfloriculture refers to souvenirs and Living Room Ornaments made from the in vitro cultured ornamental plants, which are innovative, unique, environmentally friendly, and can be produced across the year. In vitro pitcher-forming Nepenthes mirabilis will increase the attractiveness and market value of microfloriculture products. Two experiments have been carried out to stimulate in vitro pitcher formation in N. mirabilis using a completely randomized design (CRD) of a two-factorial treatment pattern with three replicates. The first experiment tested different Murashige and Skoog (MS) media formulations (full-strength, 3/4MS, 1/2MS, and 1/4MS) and phytagel concentrations (0, 2.5, 3.5, and 4.5 g l-1). The same media formulations and 6-Benzylaminopurine (BAP) concentrations (0, 0.5, 1.0, and 1.5 μM) were tested in the second experiment. The results showed that the explants cultured on 1/4MS media produced the greatest number of shoots (3.83-8.25) and leaves (26.17-26.75), the earliest pitcher formation (27.75±2.06 days), the highest number of pitchers (6.50±2.65), and pitcher-forming leaves (23.30±5.10%). Liquid media enhanced leaves (28.33±4.97) and pitchers (6.42±3.36) formation as well as pitcher-forming leaves percentage (21.37±8.01%). A 1/4MS supplemented with 0.5 μM BAP maximized pitcher-forming leaves (21.08±7.78%) and pitcher number (5.67±2.52). Adding 1.5 μM BAP on 1/4MS media produced the highest number of leaves (38.67±5.69). Full-strength MS produced the lowest number of shoots, leaves, pitchers, and pitcher-forming leaves. This study developed an affordable and effective method to improve in vitro pitcher development in N. mirabilis, highlighting how nutrient levels and BAP concentration influence pitcher formation, which aids in optimizing culture techniques for ornamental carnivorous plants.